Perfect hostage a life of Aung San Suu Kyi, Burma's prisoner of conscience - Wintle, Justin (Skyhorse Pub., 2007)
A biography of Aung San Suu Kyi, one of the world's most renowned freedom fighters and advocates of nonviolence, and the figurehead for Burma's struggle for democracy. The recipient of the Nobel Peace Prize, she has dedicated her life to helping her country.